Characterizing polymorphisms and allelic diversity of von Willebrand factor gene in the 1000 Genomes - Wang, Q. Y.; Song, J.; Gibbs, R. A.; Boerwinkle, E.; Dong, J. F.; Yu, F. L. (Journal of thrombosis and haemostasis, 2013)
Summary Background The von Willebrand factor (VWF) gene is highly polymorphic, with variants correlated with VWF antigen levels, adhesion activity, clearance and factor VIII binding. VWF mutations are detected in patients with von Willebrand disease (VWD), whereas polymorphic variants could be associated with thrombosis. However, information on the ethnic diversity of VWF variants and their association with diseases is limited. Objectives To characterize novel VWF variants from different ethnicities in the general population. Patients/Methods We analyzed samples from 1092 subjects of 14 ethnicities available in the 1000 Genomes database for VWF variants and their potential functional impacts. Results We identified 2728 SNPs and 91 insertions and deletions that had a high level of ethnic diversity, with Africans having the highest number of variants. The highest level of diversity was found in the D′ and D2 domains. Among 94 non‐synonymous variants, 31 were predicted to be deleterious, including 19 that were previously associated with VWD. Most of these ‘VWD variants’ had allele frequencies consistent with disease incidence in European subjects, but some had a significantly higher frequency in other ethnicities. The mutations R2185Q, H817Q and M740I associated with type 1 and type 2N VWD were present in more than 13% of African subjects. Conclusions These results highlight the complexity of VWF variations in different ethnic groups and emphasize the importance of interrogating variations on multiple ethnic backgrounds for associations with bleeding and thrombosis.